Calibrated ages of Fish Creek (FC) peat core from Wales - Klein, Eric S; Booth, Robert K (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland